Android Audio Recorder Mobile Application with Digital Watermarking - Lai, Boon Shien; Shamsul Kamal Ahmad Khalid (Applied Information Technology And Computer Science, 2022)
The copyright and ownership are much more important than previously as the idea of intellectual property is recognized in the world. Hence, this project focuses on designing an Android application that helps the UTHM students protect their audio presentation and music copyright using digital watermarking. The chosen SDLC to develop the application is SDLC Object-Oriented Model. The application is developed using Python, Thunkable and Airtable. The proposed application records the user text input for watermark and voice recorded and audio file uploaded. In conclusion, the proposed application may help the UTHM students to secure their audio file from unauthorized users without cost and show their ownership to their audio file when the unauthorized using is happened.